Efektivitas Pembelajaran Fisika Menggunakan Media Pembelajaran Komik Untuk Meningkatkan Kompetensi Peserta Didik - Hanifah Hanifah; Fatni Mufit (Navigation Physics : Journal of Physics Education, 2022)
Learning physics helps students connect natural phenomena with the material taught at school. Abstract physics makes it difficult for students to understand the material, so learning media is needed to convey material effectively and the latest in the form of comic-based learning media. The research method is a review of 9 journal articles published in the last 10 years. The results obtained are that there are many journals about comic media. Comic media has visual images that make it easier to convey information to readers, has a storyline that is easy to understand, systematic and organized which makes it easier for readers to follow and memorize its contents and comics can also cheer up the mood, so they are interested in reading. Comics can make learning more fun. Based on this research, it is found that physics media can increase the competence of students.